A simple expression to estimate the fatigue endurance of welded joints - Chapetti, Mirco Daniel (2018)
A simple expression is proposed to estimate the fatigue endurance of welded joints that can be used to understand and analyze in a simple way the influence of the main geometrical, mechanical and material effects (weld geometry, local geometry, material properties, residual stresses and size of defects). The proposed expression was derived from the results of the analysis of the fatigue strength of welds studied by means of a fracture mechanics approach that takes into account the fatigue behavior of short cracks by using the resistance curve method. For that purpose numerical simulation of transversely stressed butt, T and cruciform joints were performed.